Metabolism of renin-angiotensin and enkephalin in human follicular fluid: An experimental study - Maria Victoria Rodríguez Gallego; Maria Victoria Aparicio Prieto; Andrea Leza García; Juana Hernández Hernández; Jose Antonio Arizaleta Uralde; Luis Casis Sáenz (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: The relationship between the biochemical characteristics of follicular fluid (FF), oocyte quality and embryonic development has not yet been elucidated. We compared samples of FF with a normal metabolic profile against samples with metabolic abnormalities to identify potential predictive biomarkers of reproductive success. Objective: To analyze peptide activity in the FF of women undergoing in vitro fertilization using 3 samples of FF per individual. Materials and Methods: FF samples were obtained by ovum pick-up. Pathological samples were defined as samples of FF obtained from women with a gynecological condition or with infertility. A total of 30 women participated in this study. 3 samples of FF were obtained per individual (90 samples), but 8 samples were excluded because they were hemolyzed. The samples (n = 82 FF) included controls (n = 36, donors without fertility problems), women with endometriosis (n = 15), unexplained infertility (n = 19), and aged > 39 (n = 12). We assessed local encephalinergics: aminopeptidase-N (puromycin sensitive aminopeptidase and neutral endopeptidase; and components of the angiotensin system of the reproductive tract: prolyl-endopeptidase, APN, aspartate-aminopeptidase, and basic-aminopeptidase. Results: No differences were observed in peptide metabolism based on the presence or absence of oocytes in the FF. Women with endometriosis and aged > 39 yr showed alterations in puromycin sensitive aminopeptidase (p = 0.01), aminopeptidase-B (p = 0.01), aspartate-aminopeptidase (p < 0.001) and neutral endopeptidase (p < 0.001). Conclusion: This study reveals alterations in the metabolism of enkephalin and angiotensin in pathological FF, which points to these components as potential diagnostic biomarkers.